Convergent signaling pathways regulate parathyroid hormone and fibroblast growth factor-23 action on NPT2A-mediated phosphate transport - Sneddon, W. Bruce (2016)
Parathyroid hormone (PTH) and FGF23 are the primary hormones regulating acute phosphate homeostasis. Human renal proximal tubule cells (RPTECs) were used to characterize the mechanism and signaling pathways of PTH and FGF23 on phosphate transport and the role of the PDZ protein NHERF1 in mediating PTH and FGF23 effects. RPTECs express the NPT2A phosphate transporter, αKlotho, FGFR1, FGFR3, FGFR4, and the PTH receptor. FGFR1 isoforms are formed from alternate splicing of exon 3 and of exon 8 or 9 in Ir-like loop 3. Exon 3 was absent, but mRNA containing both exons 8 and 9 is present in cytoplasm. Using an FGFR1c-specific antibody together with mass spectrometry analysis, we show that RPTECs express FGFR-β1C. The data are consistent with regulated FGFR1 splicing involving a novel cytoplasmic mechanism. PTH and FGF23 inhibited phosphate transport in a concentration-dependent manner. At maximally effective concentrations, PTH and FGF23 equivalently decreased phosphate uptake and were not additive, suggesting a shared mechanism of action. Protein kinase A or C blockade prevented PTHbut notFGF23actions. Conversely, inhibitingSGK1, blocking FGFR dimerization, or knocking down Klotho expression disruptedFGF23actions but did not interfere withPTHeffects. C-terminal FGF23(180-251) competitively and selectively blocked FGF23 action without disruptingPTHeffects. However, bothPTH and FGF23-sensitive phosphate transport were abolished by NHERF1 shRNA knockdown. Extended treatment with PTH or FGF23 down-regulated NPT2A without affecting NHERF1. We conclude that FGFR1c and PTHR signaling pathways converge on NHERF1 to inhibit PTH- and FGF23-sensitive phosphate transport and down-regulate NPT2A.